Redescription of the orb-weaving spider Gasteracantha geminata (Fabricius, 1798) (Araneae, Araneidae) - Sankaran, Pradeep M.; Jobi, Malamel J.; Sebastian, Pothalil A. (Zootaxa, 2015)
The orb-weaving spider genus Gasteracantha Sundevall, 1833 (Araneidae) is notable for its pronounced sexual size dimorphism. Gasteracantha females are characterized by having a highly sclerotized “spiny” abdomen varying in relative size and number of spines, as well as abdomen dorsally and ventrally provided with varying numbers of sigillae (Cambridge 1879). The genus currently includes 70 described species and 31 subspecies (World Spider Catalog 2014). The Oriental species Gasteracantha geminata (Fabricius, 1798) was originally described from Ramnad (now known as Ramanathapuram) in Tamilnadu State of Southern India based on an unspecified number of female specimen(s). The female of this species has been described and illustrated several times by various authors. Its male is only known from the description of Simon (1895). Simon’s original description of the male of G. geminata was supported by two simple but beautiful and informative illustrations: a retrolateral view of the cephalothorax and a dorsal view of the abdomen (Simon 1895, figs. 886, 887). However we lack a clear and detailed description of the male genitalia. The present paper provides detailed redescription of G. geminata and illustrations of the male pedipalp.